2006
DOI: 10.5006/1.3280667
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Injection-Molded 17-4PH Steel in Sodium Chloride Solution

Abstract: The corrosion resistance of 17-4PH powder injection-molded (PIM) martensitic stainless steel (SS) was evaluated in naturally aerated sodium chloride (NaCl) solution (3 wt%) at 25°C. This resistance was investigated by analyzing the curves of the evolution of open-circuit potential with time (E ocp vs. time), electrochemical impedance spectroscopy (EIS), and surface observation by scanning electron microscopy (SEM) at increasing times of immersion. The susceptibility to pitting was investigated using cyclic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Immersion time is one of the most influential parameter on interface properties. Results on stainless steel related to short-term tests have been widely discussed in literature [5][6][14][15], however little has been carried out for relatively long contact periods between the electrolyte and the metallic material [16,17].…”
Section: Effect Of Immersion Timementioning
confidence: 99%
“…Immersion time is one of the most influential parameter on interface properties. Results on stainless steel related to short-term tests have been widely discussed in literature [5][6][14][15], however little has been carried out for relatively long contact periods between the electrolyte and the metallic material [16,17].…”
Section: Effect Of Immersion Timementioning
confidence: 99%
“…10) With the presence of oxide particles, the mechanical properties and corrosion resistance of the sintered stainless steels deteriorate. 2,4,11,12) Since water atomized stainless steel powders for powder injection molding (PIM) process are typically very fine in order to attain high sintered densities, the powders contain significant amounts of SiO 2 on the surface. Thus, the elimination of SiO 2 inclusions in sintered compacts has become an important focus of research.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion behavior has already been investigated for the AISI 410 SS, [5,9,[12][13][14][15] and for the 17-4 PH SS. [6,7,10,[16][17][18][19] Although some studies have demonstrated that the chemical passvation promoted an improvement on pitting corrosion resistance for other types of stainless steels, [20][21][22][23][24][25][26][27] it was not found studies relating this surface treatment to corrosion behavior of the AISI 410 and 17-4 PH SS's.…”
mentioning
confidence: 99%
“…The chemical passivation treatment did not produce significant effect on the surface roughness Ra of the studied stainless steels. Moayed et al [6] Ground surface (1200 grit), solution 3.5% NaCl, 25°C, scan rate 0.5 mV/s vs. SCE −230 Ranging from 95 to 178 -Tavakoli [16] Solution 3.5% NaCl, room temperature, scan rate 0.05 mV/s vs. SCE −120 205 -Costa et al [19] Polished surface (diamond paste 1 µm), solution 3% NaCl, 25°C, scan rate 1 mV/s vs. SCE −310 190 −115 | 829…”
mentioning
confidence: 99%